Satisfaction of Students and Parents on School Services of Catholic Schools in Southern Antique - Alda Luz N. Laureta; Dexter Paul D. Dioso (Philippine Social Science Journal, 2020)
Service quality is among the determinants that define customer satisfaction, and customer satisfaction can lead to continued customer loyalty. Understanding students' and parents' satisfaction with the student services can help the school identify their strengths and pinpoint the area that can be improved. In the Philippines, part of Catholic education is the high standard of school services. These services include the library, instructional services, information and orientation service, guidance and counseling, student organization/government and activities, student discipline, student publication, admission services, scholarship and financial assistance, food services, health services, and safety and security. Measuring the students' and parents' satisfaction level of satisfaction on school services may help maintain Catholic education's quality. Hence, the study intends to measure and compare the students' and parents' level of satisfaction with all the school services offered in Catholic schools in southern Antique for the school year 2019-2020.